Recognition of Future News in Earnings and Price Bubbles in Experimental Asset Markets. (October 2015) - Ghosh, Sudeep; Radhakrishnan, Suresh; Srinidhi, Bin; Su, Lixin (Nancy)
In this article, we use an experimental approach to examine the effect of reporting regimes on asset prices. We examine four different reporting regimes: the no recognition (NR) regime where no expected future cash flows are recognized; the full recognition (FR) regime where both the expected good news and expected bad news pertaining to the next period cash flows are recognized in current earnings; the good news recognition (GR) regime where only the expected good news pertaining to the next period cash flows are recognized in current earnings; and the bad news recognition (BR) regime where only the expected bad news pertaining to the next period cash flows are recognized in current earnings. We find that the NR, BR, and GR regimes are associated with more intense asset price bubbles than the FR regime. We also find that between the BR and GR regimes, the BR regime is associated with more intense asset price bubbles than the GR regime. Our findings shed insights about how biased (non-neutral) reporting regimes could affect the price formation process.